Seroprevalence to pathogenic leptospira in alpacas and vicuñas from Huancavelica and Ayacucho, Perú - Rosadio A., Raúl (2012)
A serologic study was conducted on 793 alpaca and 195 vicuña sera samples collected in Huancavelica and Ayacucho departments in Peru to detect specific antibodies against five pathogenic leptospira serovars (L. icterohaemorrhagiae, L. pomona, L. canicola, L. wolfii and L. ballum) by the microaglutination test. The survey revealed that 89.6% of the alpacas and 77.4% of vicuñas were positive to one or more serovars. In alpacas, the titers varied from 1:100 to 1:1600 reacting mainly to L. icterohaemorrhagiae (43.4%) and L. pomona (37.8%), whereas titers among vicuñas varied from 1:100 to 1:400 reacting similarly to L. icterohaemorrhagiae (69.2%) and L. pomona (8.2%) serovars. The alpacas also had antibodies to L. canicola (7.8 %) and L. wolfii (0.6%) serovars. These results show that the animals had previous exposure to at least 4 of the 5 serovars tested and the elevated titers to L. icterohaemorrhagiae and L. pomona serovars in alpacas suggest a recent infection event.